FRI0134 EFFECT OF JAK INHIBITORS ON PAIN AND QUALITY OF LIFE IN RHEUMATOID ARTHRITIS PATIENTS. (2nd June 2020) - Spinelli, F. R.; Garufi, C.; Ceccarelli, F.; Mancuso, S.; Duca, I.; Alessandri, C.; DI Franco, M.; Priori, R.; Riccieri, V.; Scrivo, R.; Valesini, G.; Conti, F.
Abstract : Background: Pain control is considered a treatment priority from most patients with Rheumatoid Arthritis (RA). Despite the treat to target approach, residual pain is commonly reported by patients with RA. Treatment with JAK inhibitors (JAKi) has been associated to a rapid control of pain. Objectives: To investigate the effect of JAKi on pain and quality of life in a mono-centric real-life clinical setting. Methods: Patients candidate to baricitinib or tofacitinib were evaluated at baseline and after 12 and 24 weeks of treatment. Disease activity was assessed by Disease Activity Score (DAS)28 with C reactive protein (CRP). A reduction of ≥ 50% of pain visual-analogue scale (VAS) 0-100 mm was recorded as "very much improved, substantially improved" (1). Pain VAS score ≤ 10 mm was considered "no/limited pain" (2). Patients' satisfaction was assessed by the Patient Acceptable Symptom State question (3). Data were expressed as mean (SD) or median (interquartile range) according to the variables' distribution. Mann Witney test was use and p values <0.05 were considered statistically significant. Results: Overall 108 patients started a JAK inhibitor (baricitinib n=67, tofacitinib n=41). Eighty-four patients (baricitinib n=51; tofacitinib n=33) were followed-up for at least 3 months and were included in the analysis. Table 1 summarizes demographic and clinical characteristic of the cohort. After 12 and 24 weeks of treatment we detected a significant reduction of DAS28 compared with baseline [from 4.7 (1.5) to 3.2 (1.7) 2.9 (1.5) and 2.7 (1.1), respectively; p<0.001; p<0.00001 and p<0.00001). At week 4, 27% and 51.8% of patients achieved remission and low disease activity, respectively; the percentages increase to 32.1% and 60.7% at week 12 and 42.2% and 70.3% at week 24. When evaluating the extent of reduction of the single items included in the DAS28 composite index we found that number of tender (TJ) and swollen joints (SJ) decreased from 9 (7.8) to 5 (3.5) to 4 (5) and 1 (3) at week 4, 2 (4) and 1 (3) at week 12, and 2 (4) and 1 (3) at week 24, respectively (p<0.00001 for all); the median reduction of TJC and SJC at week 4, 12 and 24 was 60%, 77% and 88%, and 81%, 86% and 100%, respectively. GH decreased from 70(30) to 40(40) at week 4, 40(30) at week 12 and 37(40) at week 24 (p<0.00001) with a median reduction of 37.5%, 44% and 46%. C reactive protein decreased by 54.5% at week 4, 47% at week 12 and 55% at week 24. VAS pain was significantly reduced at week 4, 12 and 24 [from 70(25) to 40(40, )30(40) at the three timepoints, p<0.00001] decreasing by 37.5%, 50% and 54%, respectively. A substantial reduction (≥50%) in VAS pain was reported by 41.3%, 54.4% and 53.9% of patients after 4, 12 and 24 weeks, respectively. Limited/no pain was reported by 21.3%, 24.7% and 36.5% at weeks 4, 12 and 24, respectively. Overall, 81.8% of patients achieved the PASS after a median time of 10 (7-15) days. Conclusion: JAK inhibitors baricitinib and tofacitinib induce a rapid improvement of disease activity driven both by pain and inflammation control. Even if no/limited pain was described only by one third of the patients, most of them reported a rapid and sustained reduction of pain accounting for the achievement of a satisfactory health condition. References: [1]Dworkin RH et al. Pain 2008; 9:105–121. [2]Well GA et al. J Rheumatol 2005; 32:2016–2024. [3]Heiber T et al. Ann Rheum Dis 2008; 67:967-71. Disclosure of Interests: Francesca Romana Spinelli Grant/research support from: Pfizer, Speakers bureau: Lilly, BMS, Celgene, Cristina Garufi: None declared, Fulvia Ceccarelli: None declared, Silvia Mancuso: None declared, Ilaria Duca: None declared, cristiano alessandri Grant/research support from: Pfizer, Manuela Di Franco: None declared, Roberta Priori: None declared, Valeria Riccieri: None declared, Rossana Scrivo: None declared, Guido Valesini: None declared, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi